Influence of laser radiation on optical transparent dielectrics - Levytskyi, S. M. (Physics and Chemistry of Solid State, 2020)
This paper deals with the main characteristics of the influence of pulsed laser radiation and its application for the labeling of transparent dielectrics. On the basis of the analysis of the literature data and the study of the possibilities of using laser radiation for marking different materials, it is proposed to investigate the effect of the radiation wavelength on the size of the received defect inside the material. Experimentally shown that the pulse laser processing of samples with laser irradiation energy below 3.4 mJ/cm2 visual tags in the sample are not formed. Thus, you can control the geometric dimensions of the mark.